The Effects of Country-of-Origin Research: A Bibliometric Analysis - Wu, Lingling; Madurapperuma, Wasanthi; Dissanayake, Ravindra (Information Research Communications, 2024)
Aim This research aimed to analyse the evolution and scholarly contributions related to the concept of country-of-origin (COO) by systematically reviewing peer-reviewed literature over the past five decades. Materials The study reviewed 7,468 articles published from 1973 to 2024 using specific search terms to extract data from the Web of Science Core Collection Database and Scopus. Methodology The study utilised the Bibliomerix R package and the web-based Biblioshiny, along with VOS viewer for performing quantitative bibliometric assessments and mapping scientific networks. These tools helped dissect the literature concerning Country-of- Origin (COO) through a metadata survey and by integrating text mining to trace the evolution of theoretical approaches and analytical tools. Results The findings indicate that the United States leads in scholarly output, followed by China, the United Kingdom, and Australia. Hong Kong Polytechnic University emerged as the leading institution, with a total of 77 publications. Among individual contributors, Kim S was identified as the most prolific, with a contribution of 52 articles, whereas Diamantopoulos A garnered the highest citation count with 4,678 citations. The analysis also highlighted the Theory of Planned Behaviour as the most commonly applied theoretical approach and Structural Equation Modelling as the prevalent analytical tool. Conclusions This bibliometric analysis systematically reports the primary papers, countries, affiliations, authors and key trends of publications. It also identifies the prevalent analytical tools and theoretical approaches in COO literature, providing insights into future opportunities that could reshape the dynamics of scientific COO research.
Keywords: Analytical methods; Country of origin; R tool; Text analysis; Theoretical approach